A Review of Authenticated Key Exchange Protocol Using Random Key Selection with Minimum Space Complexity - Nathaniel, Stuti; Ali, Syed Imran; Singh, Sujeet (International Journal of Computer Sciences and Engineering, 2025)
for the past decades, an extensive variety of cryptographic protocols have been suggested to resolve secure communication problems even in the occurrence of challenger. The assortment of this work varies from developing fundamental security primitives providing confidentiality and authenticity to solving more difficult, application-specific problems. With rapid developments in perimeters and potential of communications and information broadcasts, there is a rising require of authentication protocol. However, when these protocols are deployed in practice, a significant challenge is to ensure not just security but also privacy throughout these protocols’s lifetime. As computer-based devices are more extensively used and the Internet is more globally accessible, new types of applications and new types of privacy threats are being introduced to password privacy in the context of authenticated key exchange (AKE). Especially, we show that AKE protocols provably meeting the existing formal definitions do not accomplish the anticipated level of password privacy when organized in the real world.